The impact of Inequality on Economic Growth: Evidence for Mexico 1895-1994 - Roxana Gutiérrez-Romero (Verein für Socialpolitik, Ausschuss für Entwicklungsländer, 2007)
The aim of the paper is to explore the influences of initial inequality on the long run distribution of wealth. The paper presents two mathematical models that analyse the occupational choice of individuals in the presence of capital constraints and risk in entrepreneurial activities. The models show that inequality and particularly polarization hinder economic growth. The higher the initial level of polarization is, the lower the long run aggregate wealth of the economy and the higher the long run polarization will be. The models are calibrated using numerical simulations. The implications of the models are assessed empirically using data on economic growth, and income distribution in Mexico, during the period 1895-1994, as well as the "Doing Business" databases of the World Bank. Policy-wise it is found that a more egalitarian wealth distribution and less poverty can be achieved through wealth redistribution policies and by improving the business climate. This can be done by reducing the cost of setting-up firms (technology,bureaucratic and administrative costs), introducing labour-market reforms encouraging the hiring of those typically excluded such as the poor, improving the access to credit markets by reducing the costs of creating and/or registering collateral and broadening the credit bureau coverage.
Keywords: 330